TiO2 based nanocrystalline thin film gas sensors prepared by ion-assisted electron beam evaporation - Wisitsoraat A. (2014)
In this work, we develop TiO2 based nanocrystalline thin films prepared by ion-assisted ebeam evaporation process. N-type and p-type TiO 2 gassensing layers have been deposited by doping with various metal oxide materials including WO3, MoO3, and NiOx. Structural and morphological characterization by means of AFM, SEM, and XRD reveal the thin film is nanocrystalline structure with fine grain of 10-30 nm. NiOx doping with sufficiently high concentration has proven to produce p-type semiconducting thin film while WO3 and MoO3 doping results in typical n-type metal oxide semiconductor. The gas-sensing sensitivity, selectivity, and minimum detectable concentration can be effectively controlled by different dopants and doping concentrations. WO3 doped TiO 2 thin film showed high sensitivity towards NO2 acetone and ethylene at lower working temperature. In addition, TiO2-MO 3 material demonstrated good sensitivity towards CO. While p-type NiOx doped TiO2 structure show high sensitivity toward ethanol and acetone with distinct behaviors compared to other n-type TiO2 thin films. © 2007 IEEE.